Three Alba Amicorum from the Habsburg Netherlands: Manlius, Wijts, and Huenich in the Ottoman Empire - Radway, Robyn Dora (Early Modern Low Countries, 2022)
This article uses the alba collected by three travellers from the Habsburg Netherlands to Constantinople in the 1570s and 1580s to explore the purposes of collecting and what they reveal about being part of an integrated imperial mission that represented Habsburg territory abroad. The first album was gathered by the imperial ambassador’s physician Arnold Manlius between May 1571 and November 1574. Manlius’s humanist project is filled with over ninety signatures from his fellow housemates and local notables, accompanied by explanatory annotations in Latin. The article contrasts this large collection with the alba of Lambert Wijts of Mechlin and Johann Huenich of Antwerp, both of whom spent two months in Constantinople as members of tribute-carrying delegations. Wijts (who was in Constantinople between July and August 1572) and Huenich (January through March 1586) gathered eclectic collections of signatures alongside sets of costume album images. Taken together, the three alba reveal a range of collecting practices and purposes – intellectual, documentary, and personal – of men from the Southern Low Countries working in the service of Habsburg emperors in Ottoman Constantinople.